2015
DOI: 10.1007/s10661-015-5066-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of different enzyme assays and biomarkers for pollution monitoring of the marine environment

Abstract: New phosphatase and DNase inhibition tests for assessing the total pollution of a natural marine ecosystem were applied. The seawater samples with different pollution degrees were collected in the Troitsa Bay of the Peter the Great Bay (the Sea of Japan). The sensitivity of the alkaline phosphatase test to integrated pollution was in accordance with the sensitivity of the standard sea urchin sperm cell toxicity test. The increased seawater pollution level was shown to result in an up to fourfold increase in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is known that the sea cucumber's immune response is non-specific (innate) (Wang et al, 2015); there is also awareness that (after phagocytic processes) these enzymes are the body's first line of internal defence and may help in the complete degradation of exogenous substances. Our findings therefore confirm that significant increases in enzymatic activity are induced by wound-stress conditions (Seitkalieva et al, 2016).…”
Section: Enzyme Activity In CL and Cfcfsupporting
confidence: 86%
“…It is known that the sea cucumber's immune response is non-specific (innate) (Wang et al, 2015); there is also awareness that (after phagocytic processes) these enzymes are the body's first line of internal defence and may help in the complete degradation of exogenous substances. Our findings therefore confirm that significant increases in enzymatic activity are induced by wound-stress conditions (Seitkalieva et al, 2016).…”
Section: Enzyme Activity In CL and Cfcfsupporting
confidence: 86%
“…The hydrolase alkaline phosphatase (AKP) was used to evaluate the state of health of the sea cucumber (Wang et al, 2008a(Wang et al, , 2008bMazorra et al, 2002;Jing et al, 2006) and increased AKP activity was reported in sea urchin Strongylocentrotus intermedius gametes following exposure to environmental pollutants. This suggests a correlation between phosphatase concentration and environmental stress (Seitkalieva et al, 2016). In addition to hydrolase activities, cells have various mechanisms to reduce and repair damage; antioxidant enzymes are an example of this: the first line of defence against free radicals (Chainy et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Micro-organisms and enzymes from contaminated marine environments may be of particular interest, as they can function in a wide range of pH and temperature values, in the presence of metal ions, and even at high concentrations of organic solvents [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%